2009
DOI: 10.1111/j.1464-410x.2009.08867.x
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneal lymph node dissection after chemotherapy

Abstract: Retroperitoneal lymph node dissection after chemotherapy (PC‐RPLND) plays a crucial role in managing patients with advanced germ cell tumours (GCTs). In the last few years improvements in radiographic staging, a better understanding of the role of serum tumour markers, and the introduction of cisplatin‐based chemotherapy have all contributed to this surgical therapy. PC‐RPLND is necessary when residual radiographic abnormalities are present after chemotherapy. The need for a PC‐RPLND in the face of normal find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 123 publications
(181 reference statements)
2
20
0
3
Order By: Relevance
“…The incidence of viable malignant tissue, teratoma and fibrosis/necrosis reported by histopathology following RPLND is similar in our series to the ranges reported by Winter et al [20]. Most recent studies have shown the percentage of patients with residual malignant disease decreasing to between 2 and 15 %.…”
Section: Discussionsupporting
confidence: 91%
“…The incidence of viable malignant tissue, teratoma and fibrosis/necrosis reported by histopathology following RPLND is similar in our series to the ranges reported by Winter et al [20]. Most recent studies have shown the percentage of patients with residual malignant disease decreasing to between 2 and 15 %.…”
Section: Discussionsupporting
confidence: 91%
“…Although some authors suggest the possibility of performing less extensive templates for selected residual masses after chemotherapy[19], this approach has not been accepted as standard of care and we could not demonstrate a reliable pattern of dissemination to allow safe modified dissections in this setting. The presence of viable cancer post-chemotherapy varies from 4 to 20% among tertiary centers.…”
Section: Discussionmentioning
confidence: 71%
“…Fortunately, the complication rate appears to have decreased with time due to improved surgical technique and perioperative management [Winter et al 2009]. We have recently adopted an extraperitoneal approach using a midline incision in select patients undergoing PC-RPLND with a significant reduction in complications rate and hospital stay (unpublished data).…”
Section: Complications Of Pc-rplndmentioning
confidence: 99%